Chorioamnionitis disrupts erythropoietin and melatonin homeostasis through the placental-fetal-brain axis during critical developmental periods - Kitase, Yuma; Madurai, Nethra K.; Hamimi, Sarah; Hellinger, Ryan L.; Odukoya, O. Angel; Ramachandra, Sindhu; Muthukumar, Sankar; Vasan, Vikram; Sevensky, Riley; Kirk, Shannon E.; Gall, Alexander; Heck, Timothy; et al. (Frontiers in Physiology, 2023)
Introduction: Novel therapeutics are emerging to mitigate damage from perinatal brain injury (PBI). Few newborns with PBI suffer from a singular etiology. Most experience cumulative insults from prenatal inflammation, genetic and epigenetic vulnerability, toxins (opioids, other drug exposures, environmental exposure), hypoxia-ischemia, and postnatal stressors such as sepsis and seizures. Accordingly, tailoring of emerging therapeutic regimens with endogenous repair or neuro-immunomodulatory agents for individuals requires a more precise understanding of ligand, receptor-, and non-receptor-mediated regulation of essential developmental hormones. Given the recent clinical focus on neurorepair for PBI, we hypothesized that there would be injury-induced changes in erythropoietin (EPO), erythropoietin receptor (EPOR), melatonin receptor (MLTR), NAD-dependent deacetylase sirtuin-1 (SIRT1) signaling, and hypoxia inducible factors (HIF1α, HIF2α). Specifically, we predicted that EPO, EPOR, MLTR1, SIRT1, HIF1α and HIF2α alterations after chorioamnionitis (CHORIO) would reflect relative changes observed in human preterm infants. Similarly, we expected unique developmental regulation after injury that would reveal potential clues to mechanisms and timing of inflammatory and oxidative injury after CHORIO that could inform future therapeutic development to treat PBI. Methods: To induce CHORIO, a laparotomy was performed on embryonic day 18 (E18) in rats with transient uterine artery occlusion plus intra-amniotic injection of lipopolysaccharide (LPS). Placentae and fetal brains were collected at 24 h. Brains were also collected on postnatal day 2 (P2), P7, and P21. EPO, EPOR, MLTR1, SIRT1, HIF1α and HIF2α levels were quantified using a clinical electrochemiluminescent biomarker platform, qPCR, and/or RNAscope. MLT levels were quantified with liquid chromatography mass spectrometry. Results: Examination of EPO, EPOR, and MLTR1 at 24 h showed that while placental levels of EPO and MLTR1 mRNA were decreased acutely after CHORIO, cerebral levels of EPO, EPOR and MLTR1 mRNA were increased compared to control. Notably, CHORIO brains at P2 were SIRT1 mRNA deficient with increased HIF1α and HIF2α despite normalized levels of EPO, EPOR and MLTR1, and in the presence of elevated serum EPO levels. Uniquely, brain levels of EPO, EPOR and MLTR1 shifted at P7 and P21, with prominent CHORIO-induced changes in mRNA expression. Reductions at P21 were concomitant with increased serum EPO levels in CHORIO rats compared to controls and variable MLT levels. Discussion: These data reveal that commensurate with robust inflammation through the maternal placental-fetal axis, CHORIO impacts EPO, MLT, SIRT1, and HIF signal transduction defined by dynamic changes in EPO, EPOR, MLTR1, SIRT1, HIF1α and HIF2α mRNA, and EPO protein. Notably, ligand-receptor mismatch, tissue compartment differential regulation, and non-receptor-mediated signaling highlight the importance, complexity and nuance of neural and immune cell development and provide essential clues to mechanisms of injury in PBI. As the placenta, immune cells, and neural cells share many common, developmentally regulated signal transduction pathways, further studies are needed to clarify the perinatal dynamics of EPO and MLT signaling and to capitalize on therapies that target endogenous neurorepair mechanisms.